Testosterone manipulation postcastration does not alter cloacal gland growth differences in male quail selected for divergent plasma corticosterone stress response - Busso, Juan Manuel (2010)
Japanese quail selected for reduced (low-stress, LS) rather than exaggerated (high-stress, HS) plasma corticosterone response to brief restraint have consistently shown greater cloacal gland (CG) development, an androgen-dependent trait. In this study, the effects of testosterone implants on levels of plasma testosterone and CG development in castrated LS and HS quail were determined. Stress-line males were castrated and randomly allocated to 1 of 3 testosterone treatments: the empty testosterone (ET), low testosterone (LT), or high testosterone (HT) implant group. Cloacal gland volume was determined at 4 weekly intervals that represented ranges of 1 to 9 d, 8 to 17 d, 15 to 24 d, and 22 to 31 d after castration and testosterone implantation. Levels of plasma testosterone were also assessed at the end of the study. Development of the CG was affected by quail line (LS > HS), testosterone treatment (HT > LT > ET), and time of measurement (1 to 9 d < 8 to 17 d < 15 to 24 d = 22 to 31 d after castration and testosterone implantation). A significant interaction between testosterone treatment and time of measurement on CG volume was also detected (with CG volume generally increasing with time in LT and HT-treated quail, but not in ET-treated quail). However, even though HT implant treatments induced higher CG development than did LT treatments beyond the first interval of CG volume measurement, and despite the finding of greater CG volumes in LS than HS quail during the last 2 measurement intervals within each of the LT and HT groups, no interaction was observed between testosterone implant dosages and quail stress line on CG volume. Thus, by the end of the study, regardless of testosterone dose, CG volume was consistently greater in LS quail than in their HS counterparts. In addition, although, as expected, the testosterone implant treatment significantly altered levels of plasma testosterone (HT > LT > ET), neither quail line nor its interaction with testosterone treatment affected plasma testosterone. The present findings suggest that the often-observed depressed CG development in the HS line may be independent of testosterone effects.